'We believe in One, Holy, Catholic and Apostolic Church': the Armenian Apostolic perspective. Issue 2 (2nd April 2016) - Ananyan, Shahe
Abstract: This article reviews the four marks of the Church − Unity, Holiness, Catholicity and Apostolicity − from the perspective of the Armenian Apostolic historical, doctrinal and liturgical tradition, with particular reference to the importance of the total identification of church and people and drawing attention to comparisons with the ecclesiological works and treatises of Western traditions. Within the rich context of the history and liturgical life of the Armenian Orthodox Church, the author expounds the meaning of the four marks of the Church, their co-inherence and linkage with the Incarnation of Christ, which enables the Church, 'in her earthly and heavenly missions' to reflect 'the historical and mystical realities of what the apostles experienced in their mission as witnesses and teachers sent by Jesus Christ himself'.